Job Search, Efficiency Wages and Taxes - Alex Bryson; Harald Dale-Olsen (Institute of Labor Economics (IZA), 2024)
Norwegian workers' job mobility decisions are related to firms' wage policies, but also depend on the national tax schedule. By utilising Norwegian population-wide administrative linked employer-employee data on workers and firms between 2010-2019, we study how the job-to-job turnover of employees is affected by marginal taxes and firms' pay policies, enabling inferences to be made about on-the-job search. Paying higher wages is associated with a drop in job-to-job separation rates, but this negative relationship is weakened when income taxes increase. Higher taxes imply strictly reduced search activity, but less so for bonus job-workers than salaried workers.
Keywords: H24; J42; J63; M12; 330; job search; marginal taxes; monopsony; wages; effort